Interaksi Antara Defisiensi Vitamin A dan Anemia Defisiensi Zat Besi pada Anak : Perspektif Biomolekuler dan Patofisiologis - Andy Sulaiman Siregar; Arfiany Marina Nasution; Muhammad Natsir Ilvira (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Vitamin A Deficiency (VAD) and iron deficiency anemia (IDA) are global nutritional issues affecting children, particularly in developing countries. The interaction between these two conditions can lead to a more complex condition known as Vitamin A Deficiency Anemia (VADA). This study aims to review the molecular relationship between Vitamin A deficiency and iron metabolism leading to VADA, as well as its impact on children's health. The methodology used in this article is a literature review of various clinical studies, epidemiological research, and relevant molecular experiments. The results show that VADA is primarily a functional iron deficiency, where iron absorption is impaired despite overall body iron levels not being critically low. This mechanism involves the regulation of hepcidin, redistribution of iron, and its effects on erythropoiesis. Additionally, therapy with Vitamin A supplementation has been shown to increase erythropoietin and hemoglobin production in children with dual deficiencies. The implications of these findings highlight the need for more integrated therapeutic strategies that consider both Vitamin A and iron status simultaneously. Further research is needed to understand the molecular mechanisms more deeply involved in this interaction and to develop more effective therapies for children with VADA.